The Effect of Code Stemi Program on Door to Balloon Time in Patients with St Elevation Myocardial Infarction in Manado City - Sarippy, Jesseline; Yuly Peristiowati; Rahmania Ambarika (STRADA : Jurnal Ilmiah Kesehatan, 2025)
ST-Elevation Myocardial Infarction (STEMI) is a life-threatening cardiovascular emergency that requires rapid and appropriate intervention. One key indicator of successful management is Door-to-Balloon Time (D2BT), which reflects the interval between a patient's arrival at the emergency department and the initiation of primary percutaneous coronary intervention. The CODE STEMI program was developed to streamline the clinical pathway and accelerate reperfusion therapy. To evaluate the impact of the CODE STEMI program on achieving optimal D2BT in STEMI patients. This quantitative comparative study employed an analytical design using the Chi-Square test.